Adaptive humoral immune response and cellular immune status in cancer patients and patients under immunosuppression vaccinated against SARS-CoV-2. (2nd November 2022) - Kos, Igor Age; Kiefer, Maximilian; Brill, Katharina; Cetin, Onur; Bittenbring, Joerg Thomas; Ahlgrimm, Manfred; Smola, Sigrun; Lohse, Stefan; Christofyllakis, Konstantinos; Kaddu-Mulindwa, Dominic; Neumann, Frank; Bewarder, Moritz; et al.
ABSTRACT: Background: Patients with cancer and autoimmune diseases are at higher risk of severe COVID-19. They may not develop protective immune responses following vaccination. We investigated patients' cellular and humoral immune response after two COVID-19 vaccine doses. Research design and methods: Subjects were stratified into subgroups according to therapy and grade of immunosuppression at time of vaccination. Results: Antibody titers were compared to healthy controls. 32/122 (26%) did not develop detectable antibody titers. Of these, 22 (66.6%) had active therapy. Patients showed significant lower antibody titers compared to controls (median 790 vs. 3923 AU/mL, p = 0.026). Patients with active therapy had significant lower antibody titers compared to those without (median 302 vs. 3952 U/L P < 0.001). B-cell count was lower in the group without antibody titers (median 29.97 vs. 152.8; p = 0.002). 100% of patients under anti-CD20 therapy had no detectable antibody titer, followed by anti-TNF (66%), BTK inhibitors (50%), ruxolitinib (35.5%), TKI (14.2%), and lenalidomide (12.5%). Anti-CD20 therapy, ruxolitinib, BTK inhibitors, and anti-CD38 therapy presented significant lower antibody titers compared to controls. Conclusions: Patients undergoing therapy for cancer or autoimmune diseases are at higher risk of insufficient humoral immune response following COVID-19 vaccination. Furthermore, alterations in the B-cell compartment correlate with lower antibody titers.